2012
DOI: 10.1002/chem.201200624
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Polypyridyl Complexes Hopping at Anionic Lipid Bilayers through a Supramolecular Bond Sensitive to Visible Light

Abstract: The new ruthenium complex [Ru(terpy)(dcbpy)(Hmte)](PF(6))(2) ([2](PF(6))(2); dcbpy=6,6'-dichloro-2,2'-bipyridine, terpy=2,2';6',2"-terpyridine, Hmte=2-(methylthio)ethanol) was synthesized. In the crystal structure, this complex is highly distorted, revealing steric congestion between dcbpy and Hmte. In water, [2](2+) forms spontaneously by reacting Hmte and the aqua complex [Ru(terpy)(dcbpy)(OH(2))](2+) ([1](2+)), with a second-order rate constant of 0.025 s(-1) M(-1) at 25 °C. In the dark, the Ru-S bond of [2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 77 publications
3
44
0
Order By: Relevance
“…The synthesis of all described ligands and complexes was performed as reported previously. 3β‐(2‐{2‐[2‐(Methylthio)ethoxy]ethoxy}ethoxy)cholesterol ( 2 ; CAS‐Nr: 1373125‐91‐7) was described by Bahreman et al . [Ru(tpy)(bpy)(Cl)]Cl and [ 1 ](PF 6 ) 2 were synthesized according to previous reports, and [ 3 ](PF 6 ) 2 was prepared as described by Askes et al .…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of all described ligands and complexes was performed as reported previously. 3β‐(2‐{2‐[2‐(Methylthio)ethoxy]ethoxy}ethoxy)cholesterol ( 2 ; CAS‐Nr: 1373125‐91‐7) was described by Bahreman et al . [Ru(tpy)(bpy)(Cl)]Cl and [ 1 ](PF 6 ) 2 were synthesized according to previous reports, and [ 3 ](PF 6 ) 2 was prepared as described by Askes et al .…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, centrifugation experiments also showed that dicationic ruthenium aqua complexes interact significantly with negatively charged lipid bilayers even in the absence of thioether-cholesterol ligand. [34,35] These results suggested that adsorption of the bicationic ruthenium complexes to negatively charged bilayers may play a role in the mechanism of the coordination reaction of membrane-embedded sulfur ligands. However, it has up to now been impossible to detect such adsorption, notably because the changes occurring in the coordination sphere of the metal upon adsorption are not significant enough to allow detection by UV/Vis spectroscopy.…”
Section: Introductionmentioning
confidence: 90%
“…By dissolving [Ru(terpy)(dcbpy)(Cl)]Cl in an aqueous solution, the chloride ligand coordinated to ruthenium is quickly and quantitatively substituted by an aqua ligand to form [2] 2 + and two chloride anions. [35,36] Thus, replacing [2](PF 6 ) 2 by [Ru(terpy)(dcbpy)(Cl)]Cl allows for preparing 5 mm solutions of [2] 2 + with chloride counter anions instead of PF 6 À .…”
Section: Itc Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,28,34,36,50,51 Apart from Ru(bpy) 2 , Ru(II)-based photocaging groups are frequently composed of bi- or tridentate ancillary ligands, including 2,2′:6′,2″-terpyridine (tpy) and 1,10-phenanthroline (phen). 8,21,28,35,39,52,53 These imine-based photocages have been effectively applied to release bioactive molecules bearing nitriles, thioethers, and aromatic heterocycles, which generally cannot be protected by traditional organic photocages.…”
Section: Introductionmentioning
confidence: 99%